2017
DOI: 10.11118/actaun201664062095
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' Markets: Positive Feelings of Instagram Posts

Abstract: PILAŘ LADISLAV, BALCAROVÁ TEREZA, ROJÍK STANISLAV. 2016. Farmers' Markets: Positive Feelings of Instagram Posts. Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 64(6): 2095-2100.With increasing consumer requirements, farmers and vendors see the importance of social media as a marketing tool to engage with consumers. In particular, on a more personal level for reasons of brand management. Instagram is becoming increasingly popular as a marketing communication tool. The aim of this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…People through social networks share not only photos, but also personal experiences, opinions, preferences, activities and feelings are shared among friends. Hashtags are used to mark keywords or topics within a microblog and have proven to be useful for many applications (Efron, 2010) or sentiment analysis (Wang et al, 2011;Pilař et al, 2016b). Other authors claim that hashtag can be described as a technomorpheme: it is a linguistic segment as well as a clickable hyperlink, which allows the creation of a network (Giaxoglou, 2018).…”
Section: Electronic Issnmentioning
confidence: 99%
“…People through social networks share not only photos, but also personal experiences, opinions, preferences, activities and feelings are shared among friends. Hashtags are used to mark keywords or topics within a microblog and have proven to be useful for many applications (Efron, 2010) or sentiment analysis (Wang et al, 2011;Pilař et al, 2016b). Other authors claim that hashtag can be described as a technomorpheme: it is a linguistic segment as well as a clickable hyperlink, which allows the creation of a network (Giaxoglou, 2018).…”
Section: Electronic Issnmentioning
confidence: 99%
“…• regarding the question what would affect them for their purchase, answers were mostly the classic forms of marketing communication, such as recommendations from friends, more interesting form of promotion and tasting. This seems to us quite surprising, because currently it is said that consumers are active creators of communication content and not just passive receivers of messages and that social media are used more often due to the fact that they have boosted marketing practices, such as advertising and promotion, their unmatched features and enormous popularity [84,85]. However, as our research suggests, private labels are an exception.…”
Section: Discussionmentioning
confidence: 89%
“…The analysis of Instagram ® posts made by Pilař et al . (2016) with more than 1 million words revealed that the terms ‘healthy’, ‘great’ and ‘good’ were commonly used in photographs together with the terms ‘organic’, ‘vegan’, ‘fresh’, ‘local’, ‘gluten free’, ‘delicious’, bringing a positive feeling to these descriptors. In fact, it is widely acknowledged that the name given to a food can affect subsequent evaluations and impressions of it (Bryant & Barnett, 2019).…”
Section: Resultsmentioning
confidence: 99%